2017
DOI: 10.1074/jbc.m117.776260
|View full text |Cite
|
Sign up to set email alerts
|

A new long noncoding RNA (lncRNA) is induced in cutaneous squamous cell carcinoma and down-regulates several anticancer and cell differentiation genes in mouse

Abstract: Keratinocyte-derived cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer. Although some of the early events involved in this pathology have been identified, the subsequent steps leading to tumor development are poorly defined. We demonstrate here that the development of mouse tumors induced by the concomitant application of a carcinogen and a tumor promoter (7,12-dimethylbenz[]anthracene (DMBA) and 12--tetradecanoylphorbol-13-acetate (TPA), respectively) is associated with the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 62 publications
(63 reference statements)
1
28
0
Order By: Relevance
“…BASP1 is also downregulated in lung cancer by specific miR‐191‐mediated mRNA degradation (Xu et al , ). In mouse, BASP1 is downregulated among several other anticancer genes in induced cutaneous squamous cell carcinoma by the long noncoding RNA AK144841 (Ponzio et al , ). Recently, tumor‐suppressive functions of BASP1 have been observed in several human cancer cell types.…”
Section: Introductionmentioning
confidence: 99%
“…BASP1 is also downregulated in lung cancer by specific miR‐191‐mediated mRNA degradation (Xu et al , ). In mouse, BASP1 is downregulated among several other anticancer genes in induced cutaneous squamous cell carcinoma by the long noncoding RNA AK144841 (Ponzio et al , ). Recently, tumor‐suppressive functions of BASP1 have been observed in several human cancer cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing reports demonstrated that the aberrant expression of lncRNAs exert tumor-promoting or tumor-suppressive effects on different types of cancers [ 8 , 9 ]. Moreover, recent evidence revealed that lncRNAs can be involved in the regulation of several cellular processes, such as cell proliferation, cell cycle, differentiation and apoptosis [ 10 , 11 ]. For example, long noncoding RNA LINC00261 suppresses cell proliferation and invasion and promotes cell apoptosis in human choriocarcinoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that lncRNAs are crucial factors in tissue physiology and the pathological processes of various diseases, including cancer (6,7). A large number of dysregulated lncRNAs have been identified in cancer, suggesting their oncogenic or tumor-suppressive properties (8,9). lncRNAs have been reported to serve an important role in the oncogenesis and progression of TC (10,11).…”
Section: Introductionmentioning
confidence: 99%